Middle latency auditory-evoked potential index monitoring of cerebral function to predict functional outcome after emergency craniotomy in patients with brain damage. Issue 1 (December 2015) - Tsurukiri, Junya; Nagata, Katsuhiro; Hoshiai, Akira; Oomura, Taishi; Jimbo, Hiroyuki; Ikeda, Yukio
Abstract Background At present, no satisfactory reports on the monitoring of cerebral function to predict functional outcomes after brain damage such as traumatic brain injury (TBI) and stroke. The middle latency auditory-evoked potential index (MLAEPi) monitor (aepEX plus®, Audiomex, UK) is a mobile MLAEP monitor measuring the degree of consciousness that is represented by numerical values. Hence, we hypothesized that MLAEPi predicts neurological outcome after emergency craniotomy among patients with disturbance of consciousness (DOC), which was caused by brain damage. Methods The afore-mentioned patients who underwent emergency craniotomy within 12 h of brain damage and were subsequently monitored using MLAEPi were enrolled in this study. DOC was defined as an initial Glasgow Coma Scale score < 8. MLAEPi was measured for 14 days after craniotomy. Neurological outcome was evaluated before discharge using a cerebral performance category (CPC) score and classified into three groups: favorable outcome group for a CPC score of 1 or 2, unfavorable outcome group for a score of 3 or 4, and brain dead (BD) group for a score of 5. Results Thirty-two patients were included in this study (17 with TBIs and 15 with acute stroke). Regarding outcome, 10 patients had a favorable outcome, 15 had an unfavorable outcome, and 7 were pronounced BD. MLAEPi was observed to be significantly higher on day 5 than that observed immediately after craniotomy in cases of favorable or unfavorable outcome (63 ± 3.5 vs. 36 ± 2.5 in favorable outcome; 63 ± 3.5 vs. 34 ± 1.8 in unfavorable outcome). MLAEPi was significantly lower in BD patients than in those with a favorable or unfavorable outcome on day 3 (24 ± 4.2 in BD vs. 52 ± 5.2 and 45 ± 2.7 in favorable and unfavorable outcome, respectively) and after day 4. MLAEPi was significantly higher in patients with a favorable outcome than in those with a favorable or unfavorable outcome after day 6 (68 ± 2.3 in favorable outcome vs. 48 ± 2.3 in unfavorable outcome). Conclusion We believe that MLAEPi satisfactorily denotes cerebral function and predicts outcomes after emergency craniotomy in patients with DOC, which was caused by acute brain damage.